The Present (Journal of Parents and Teachers, 2024)
The short film centers on a teenager who rarely ventures outside, spending most of his time playing video games in his dimly lit living room. Completely absorbed in the screen, he barely notices his mother rushing in from work. She greets him, suggests he take a break from his game, and raises the blinds to let in some light. Apologizing for her tardiness, she presents him with a gift.When the boy opens the box, he’s initially thrilled to find a small puppy inside. However, his excitement quickly fades when he discovers that the puppy is missing one of its legs. Upset, he discards the pet and tries to ignore it. Undeterred, the puppy relentlessly seeks his attention, refusing to give up until it wins him over.
Keywords: education; short film; family; adolescence; video games; leisure; inclusion; animal therapy; self-improvement